2019
DOI: 10.1111/1750-3841.14802
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic Heating of Lemon and Grapefruit Juices Under Vacuum Pressure— Comparison of Electrical Conductivity and Heating Rate

Abstract: Ohmic heating fundamentally depends on electrical conductivity. In this study, grapefruit and lemon juices were ohmically heated under vacuum conditions. The electrical conductivity was measured at voltage gradients (10, 20, and 30 V/cm) and vacuum pressure (0 [atmospheric pressure], −30, and −60 kPa) for four temperature ranges (30, 40, 50, and 60 °C), meanwhile the heating rate was also reported at the same level of pressure and voltage gradient. The electrical conductivity and heating rate considerably vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…A linear increase in electrical conductivity was observed following the temperature elevation during ohmic heating. The result obtained in this study was consistent with the previous studies which demonstrated that electrical conductivity of tomato concentrate increased linearly with the heating temperature as a result of reduced drag force of ionic compounds inside the product [Fadavi & Salari, 2019]. Electrical conductivity is affected by the ionic compounds of the product.…”
Section: Results and Discussion The Electrical Conductivity Of Mulberry Pureesupporting
confidence: 92%
“…A linear increase in electrical conductivity was observed following the temperature elevation during ohmic heating. The result obtained in this study was consistent with the previous studies which demonstrated that electrical conductivity of tomato concentrate increased linearly with the heating temperature as a result of reduced drag force of ionic compounds inside the product [Fadavi & Salari, 2019]. Electrical conductivity is affected by the ionic compounds of the product.…”
Section: Results and Discussion The Electrical Conductivity Of Mulberry Pureesupporting
confidence: 92%
“…Concerning the OH processing action mode, it is based on electromagnetic methods such as, i.e., radioactive dielectric, capacitive dielectric, radioactive magnetic, and inductive heating ones ( Fig. 2 ) [60] . Moreover, OH processing is similar, to some extent, to the microwave heating systems at different frequencies [61] .…”
Section: Ohmic Heating (Oh)mentioning
confidence: 99%
“…2 Schematic diagram of the ohmic heating (OH) processing system; (1) power unit, (2) power analyzer, (3) computer, (4) thermocouple, (5) cell, (6) electrode, (7) glass dome, (8) vacuum pump, (9) buffer tank, (10) valve, (11) vacuum gauge, (12) needle valve. Adapted from Fadavi and Salari [60] with permission. …”
Section: Ohmic Heating (Oh)mentioning
confidence: 99%
“…The reason for the low electrical current passing through sample at OHVC can be attributed to the rate of bubbles expansion (Fadavi & Salari, 2019; Fadavi et al ., 2020). The effect of vacuum decreases the pressure difference inside and outside the bubbles; therefore, bubbles expansion will be more rapid and as a result their escape from the surface of media is facilitated, interrupting the passage of current through the sample (Fadavi & Salari, 2019). Also, it could be noted that the sample heat capacity and latent heat of vaporisation were a function of the pressure inside the heating chamber.…”
Section: Results and Decisionmentioning
confidence: 99%